Did the ptolemaic imperial politics influence the language of the septuagint? - Gienini, Olga A. (2022)
Fil: Gienini, Olga A. Pontificia Universidad Católica Argentina. Centro de Estudios de Historia del Antiguo Oriente; Argentina